The effects of leukoreduction on canine blood unit weight and processing time. Issue 6 (17th June 2022) - Trinder, Richard D.; Lo, Eva; Humm, Karen R.
Abstract: Background: Despite a lack of strong evidence of benefit, leukoreduction is employed to decrease the risk of leukocyte‐induced transfusion reactions. However, the impact of leukoreduction on blood bank costs and inventory management is not well understood. The purpose of this study was to determine whether leukoreduction of whole blood increases total processing time and weight loss from packed red blood cells (PRBCs) and plasma relative to bags created from nonleukoreduced whole blood. Key findings: A total of 68 canine whole blood collections were divided equally into leukoreduced and nonleukoreduced groups (N = 34 in each). There was no significant difference between groups in mean PRBC or plasma unit weights or processing times. Leukoreduced PRBC bags lost a significantly greater proportion of weight during processing than did nonleukoreduced PRBC bags ( P < 0.01), which is attributed to red and white blood cells lost in the filtration process. Significance: Leukoreduction did not lead to a significant increase in processing times or smaller PRBCs or plasma bags compared to nonleukoreduced bags. The blood remaining in the leukoreduction filter following filtration is primarily composed of red blood cells, with minimal plasma retained.